2008
DOI: 10.1111/j.1365-313x.2008.03575.x
|View full text |Cite
|
Sign up to set email alerts
|

Knock‐down of the MEP pathway isogene 1‐deoxy‐d‐xylulose 5‐phosphate synthase 2 inhibits formation of arbuscular mycorrhiza‐induced apocarotenoids, and abolishes normal expression of mycorrhiza‐specific plant marker genes

Abstract: SummaryThe first step of the plastidial methylerythritol phosphate (MEP) pathway is catalyzed by two isoforms of 1-deoxy-D-xylulose 5-phosphate synthase (DXS1 and DXS2). In Medicago truncatula, MtDXS1 and MtDXS2 genes exhibit completely different expression patterns. Most prominently, colonization by arbuscular mycorrhizal (AM) fungi induces the accumulation of certain apocarotenoids (cyclohexenone and mycorradicin derivatives) correlated with the expression of MtDXS2 but not of MtDXS1. To prove a distinct fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 63 publications
6
52
0
Order By: Relevance
“…Here, the generally highly branched intraradical hyphal network is less differentiated, accompanied by alterations in fungal root occupancy, the timing of infection, fungal development, and, most strikingly, in the longevity of the asynchronous AM symbiosis. This arbuscule phenotype matches observations for M. truncatula plants depleted in the AM marker genes MtPT4 (Javot et al, 2007) and MtDsx2 (Floß et al, 2008). Since during nodulation, MtSucS1-as plants also exhibited early symbiosome senescence (Baier et al, 2007), MtSucS1 is likely involved in the C supply to microsymbionts and in the sufficient development of endosymbiotic interfaces in general.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Here, the generally highly branched intraradical hyphal network is less differentiated, accompanied by alterations in fungal root occupancy, the timing of infection, fungal development, and, most strikingly, in the longevity of the asynchronous AM symbiosis. This arbuscule phenotype matches observations for M. truncatula plants depleted in the AM marker genes MtPT4 (Javot et al, 2007) and MtDsx2 (Floß et al, 2008). Since during nodulation, MtSucS1-as plants also exhibited early symbiosome senescence (Baier et al, 2007), MtSucS1 is likely involved in the C supply to microsymbionts and in the sufficient development of endosymbiotic interfaces in general.…”
Section: Discussionsupporting
confidence: 60%
“…4, C-K). In mycorrhizal controls, the distribution of the stages young, mature, degenerating, and dead arbuscules (Floß et al, 2008) was 1:2.3:1.4:1.1 (Fig. 4L), depicting a successive colonization process with balanced rates of arbuscule decay and reemergence.…”
Section: Antisensing Mtsucs1 Leads To a Higher Proportion Of Senescinmentioning
confidence: 99%
See 1 more Smart Citation
“…Data mining revealed that only six regulators (MT000013, MT003698, MT006389, MT007392, MT009598, MT015410) were also up-regulated during the arbuscular mycorrhizal symbiosis [29], [66], [67]. These were distributed between six TF families and four regulation classes (“bacA”, “diff2”, “fix+” and “NN”) and all of them were also expressed in non symbiotic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of AM, these have been named mycorradicins and identified as acyclic C14 apocarotenoid polyenes (Bothe et al 1994 ;Klinger et al 1995a ;Schliemann et al 2006) . Although Fester et al (2002a) demonstrated that some highly mycorrhizal roots may completely lack mycorradicin, apocarotenoid synthesis seems to be important for AM establishment because mutants deficient of (Fester et al 2002a) or with reduced carotenoid biosynthesis capacity (Fester 2008) show a reduced development of functional symbiotic structures (Floß et al 2008) . In addition to mycorradicins, esterified mycorradicins and glycosylated C13 cyclohexenone apocarotenoid derivatives can accumulate in mycorrhizal tissues (Maier et al 1995 ;Strack and Fester 2006 ;Schliemann et al 2008) .…”
Section: Secondary Apocarotenoidsmentioning
confidence: 99%